Affordances of homeschool journey in rural environment for children's performances - Yatiman, Noor Ain (2012)
The study investigated children's performances during homeschool journey in a rural environment through their actualized affordances at a village in Johor, Malaysia. The study was conducted with fifty-four middle childhood children through drawings, interviews and participant observation. The data were analyzed using qualitative content analysis. Children engaged more with natural elements rather than manmade elements and positively perceived, utilized and shaped the affordances. Therefore there is evidence to suggest that children recognized homeschool journey as their play spaces allowing them to interact with nature and developed their physical, social and cognitive skills, especially for children with high independent mobility.